Common Sleep Disorders in Children - Chawla, Jasneek K.; Heussler, Helen (Journal of Pediatric Biochemistry, 2016)
Sleep disorders are common in children and include both respiratory and non-respiratory causes. An awareness of these conditions is important due to the recognized complications of untreated sleep disorders in childhood. This review provides an overview of common sleep disorders in childhood including an overview of treatment options.
Keywords: sleep; breathing; childhood; pediatrics